Wesley Winans Stout papers - Stout, Wesley Winans, 1890-; Lorimer, George Horace, 1869-1937.
Chiefly editorial correspondence of Stout and his predecessor, George Horace Lorimer, and other members of the Saturday Evening Post editorial staff including Thomas B. Costain and Francis Churchill "Churchie" Williams. Correspondence pertains primarily to proposals, assignments, submission, acceptance, or rejection of articles and fiction for the magazine. Includes papers concerning Stout's activities after leaving the Post. Correspondents include Joseph Alsop, Arthur "Bugs" Baer, Thomas Beer, Albert Jeremiah Beveridge, William Jennings Bryan, William Faulkner, Edna Ferber, Joseph Hergesheimer, De Wolf Hopper, Ring Lardner, John P. Marquand, Will Rogers and family, Eleanor Roosevelt, Franklin D. Roosevelt, Pierre Salinger, Robert W. Service, Julian Street, and Woodrow Wilson.
Editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alsop, Joseph, -- 1910-1989 -- Correspondence; Baer, Arthur, -- 1886-1969 -- Correspondence; Beer, Thomas, -- 1889-1940 -- Correspondence; Beveridge, Albert Jeremiah, -- 1862-1927 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Costain, Thomas B. -- 1885-1965 -- Correspondence; Faulkner, William, -- 1897-1962 -- Correspondence; Ferber, Edna, -- 1887-1968 -- Correspondence; Hergesheimer, Joseph, -- 1880-1954 -- Correspondence; Hopper, De Wolf, -- 1858-1935 -- Correspondence; Lardner, Ring, -- 1885-1933 -- Correspondence; Lorimer, George Horace, -- 1869-1937 -- Correspondence; Marquand, John P. -- 1893-1960 -- Correspondence; Rogers, Will, -- 1879-1935 -- Correspondence; Roosevelt, Eleanor, -- 1884-1962 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Salinger, Pierre -- Correspondence; Service, Robert W. -- 1874-1958 -- Correspondence; Street, Julian, -- 1879-1947 -- Correspondence; Williams, Francis Churchill, -- 1869-1945 -- Correspondence; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Rogers family -- Correspondence; Saturday evening post; American periodicals; Editors